2019
DOI: 10.1186/s12934-019-1256-0
|View full text |Cite
|
Sign up to set email alerts
|

Fhl1p protein, a positive transcription factor in Pichia pastoris, enhances the expression of recombinant proteins

Abstract: BackgroundThe methylotrophic yeast Pichia pastoris is well-known for the production of a broad spectrum of functional types of heterologous proteins including enzymes, antigens, engineered antibody fragments, and next gen protein scaffolds and many transcription factors are utilized to address the burden caused by the high expression of heterologous proteins. In this article, a novel P. pastoris transcription factor currently annotated as Fhl1p, an activator of ribosome biosynthesis processing, was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Our first step was to find a proper P. pastoris strain. Although the strain P. pastoris GS115 was reported as a robust host to express recombinant proteins (Gurramkonda et al, 2009;Nie et al, 2014;Zheng et al, 2019;Wang et al, 2020), cell extracts prepared from this strain showed relatively little protein synthesis activity with very low and unreliable yields of sfGFP (data not shown). Then, we switched to the strain P. pastoris SMD1163 (pep4 prb1), which is derived from GS115 with knocking out of two protease genes (pep4 encodes protease A and prb1 encodes protease B) (Gleeson et al, 1998).…”
Section: Development Of An Initial P Pastoris-based Cfps Systemmentioning
confidence: 98%
“…Our first step was to find a proper P. pastoris strain. Although the strain P. pastoris GS115 was reported as a robust host to express recombinant proteins (Gurramkonda et al, 2009;Nie et al, 2014;Zheng et al, 2019;Wang et al, 2020), cell extracts prepared from this strain showed relatively little protein synthesis activity with very low and unreliable yields of sfGFP (data not shown). Then, we switched to the strain P. pastoris SMD1163 (pep4 prb1), which is derived from GS115 with knocking out of two protease genes (pep4 encodes protease A and prb1 encodes protease B) (Gleeson et al, 1998).…”
Section: Development Of An Initial P Pastoris-based Cfps Systemmentioning
confidence: 98%
“…In a previous study in our laboratory, Zheng et al also proposed a novel yeast transcription factor, tentatively named Fhl1p, implicated in the regulation of rRNA processing genes and genes related to ribosomal small/large subunit biogenesis genes. This factor was found to facilitate the translation e ciency of exogenous proteins (Zheng et al 2019).…”
Section: Effect Of Overexpression Of Cofactors On Recombinant Pmgl-ba...mentioning
confidence: 99%
“…Consequently, the modulation of expression of genes encoding transcriptional regulators offers a variety of alternatives enabling an increment in the rProt production yield. However, the high number of genes affected by the modulated expression of these factors should be considered [76,79,103]. Given that, in general, the comparisons are performed under optimised process conditions for the wild-type strain, the results obtained by adapting the bioprocess to other transcriptional variants of K. phaffii are unknown [23].…”
Section: Transcription Factor Engineering In K Phaffii For Recombinan...mentioning
confidence: 99%